An integrated approach for added-value products from lignocellulosic biorefineries : vanillin, syringaldehyde, polyphenols and polyurethane /: vanillin, syringaldehyde, polyphenols and polyurethane. ([2018]) - Rodrigues, Alírio Egídio; Pinto, Paula Cristina de Oliveira Rodrigues; Barreiro, Maria Filomena; Esteves da Costa, Carina Andreia; Ferreira da Mota, Maria Inês; Fernandes, Isabel
No abstract available